Analisis Kinerja Keuangan Terhadap Nilai perusahaan ,Struktur Modal Sebagai Variabel Intervening - Naufal Rizky Muhammad Albani; Nur Endah Fajar Hidayah (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to analyze the effect of financial performance, proxied by profitability (ROA) and liquidity (CR), on firm value measured by Tobin’s Q, with capital structure (DER) as a mediating variable. The research sample consists of 18 startup companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. The method employed is panel data regression analysis, with the best model selected through the Chow Test, Hausman Test, and Lagrange Multiplier Test. The findings indicate that profitability and liquidity have a significant effect on capital structure. However, profitability, liquidity, and capital structure are not proven to have a direct effect on firm value. Furthermore, capital structure does not serve as a mediating variable. These results suggest that traditional financial metrics are not the main factors in assessing startup valuation in the Indonesian capital market. Other aspects, such as growth prospects and innovation, appear to play a more dominant role in determining firm value